Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15

Studies on optimization of cultural conditions and effect of media constituents on production of intracellular penicillin V acylase from Erwinia aroideae (DSMZ 30186) - Atul, Kumar; Vivek, Lonkar; Archana, Pundle (Research Journal of Biotechnology, 2008)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme. Erwinia aroideae (DSMZ 30186) produced high levels of intracellular penicillin V acylase. Amongst various carbon sources used (2.0 %); fructose, galactose, sucrose and mannitol increased enzyme production up to 579, 544, 534 and 504 IU/g dry weight (DW), respectively, compared to minimal media (263 IU/g DW); however maximum PVA productivity (2796 IU/ L) was achieved using fructose. Ammonium ions escalated the enzyme production to 1266.9 IU/g DW; however sodium glutamate was the best nitrogen source for overall productivity of enzyme (2045 IU/ L). Cornsteep liquor and skim milk were used as supplements; 1.0 % cornsteep liquor and 3.0 % skim milk were optimum for the production of PVA up to 823 and 93 IU/g DW, respectively. Optimum cultural conditions for the production of PVA from E. aroideae were standardized. Erwinia aroideae produced 1543 IU/g DW penicillin V acylase in Erlenmeyer flasks (250 ml) containing 50 ml of minimal medium with 0.3% ammonium sulphate, pH 7. 0 at 28 degrees C and 180 rpm when incubated for 56 hr.
Keywords: carbon sources; Erwinia aroideae; intracellular; nitrogen sources; Penicillin V acylase